Vulnerability of small forest patches to fire in the Paraiba do Sul River Valley, southeast Brazil: Implications for restoration of the Atlantic Forest biome - Guedes, Betina J. [UNESP]; Massi, Klécia G. [UNESP]; Evers, Cody; Nielsen-Pincus, Max (Elsevier, 2020)
The Atlantic Forest biome, a biodiversity hotspot historically threatened by deforestation and human disturbance, has recently seen a net gain in native forest cover due to changes in land use, enactment of new laws, and substantial investment in restoration. Like many South American and global ecosystems, the Atlantic Forest biome has also experienced an increase in area burned by wildfire largely due to human ignitions, which threatens these gains. Our objective was to understand the vulnerability of protected areas and small patches of neotropical forest to fire in the Paraíba do Sul River Valley, Brazil, a region within the Atlantic Forest biome. Our modeled fire behavior and growth was calibrated to the observed fire size record and simulated fire perimeters that varied from 1-ha to more than 2250-ha. We found a strong positive correlation between pasture area and burn probability, and a negative correlation between burn probability and forest cover, reinforcing the role of pastures in fire ignition and transmission to forest edges and small fragmented patches. While most tropical forest patches (85%) were less than 10 ha, these forest patches only comprised a small portion (10%) of the total forest cover but were most vulnerable to fire exposure. The variables most influential on burn probability were patch size and distance to edge. Specifically, fires were most frequent in patches less than 100-ha in size and relatively absent in patches greater than 1000-ha. Likewise, fires occurred within 180-m of forest patch edges and exposure was minimal deeper into forest patches. Exposure was highest in stands with canopy-cover less than 20%, and then declined monotonically until 90%, after which burn probability was minimal. Our results demonstrate that the relationship between fire and landscape patterns are strongly contingent in Atlantic Forest landscape, where degraded tropical forests are often comprised of small forest patches, large patch edges, and low canopy cover, all of which increase the vulnerability of tropical forest to burning in Southeast Atlantic forest. Continued management of fire is critical to preserving the recovery and securing investments in reforestation in the Atlantic Forest biome.
Keywords: Burning; Edge; Fragment; Pasture; Tropical rainforest